KEWENANGAN MAHKAMAH AGUNG DALAM EKSISTENSI PEMBINAAN HAKIM MILITER PADA PENYELESAIAN SENGKETA TATA USAHA MILITER - Raditya Feda Rifandhana (University of Merdeka Malang, 2017)
Indonesia is a state of law in the formation of the constitutional state is mandated by the constitution, state lawcan not be separated from the court has the authority to resolve the issue or dispute, in the common cases likeweddings resolved in religious courts, cases related to state the administration disputes resolved state administrativecourt, but the realm of the dispute to the field of infringement decisions of military rule finalized inAdministrativeCourts military, for now the Supreme Court in cooperation with the military Court Highalongwith the military Court more by providing technical guidance judiciary to the military judge inresolvingdisputes and the administration of military in the form of education and training